PERSEPSI MAHASISWA TERHADAP PENGARUH PENGGUNAAN INSTAGRAM DALAM PEMBELAJARAN BAHASA INGGRIS - Liany, Gladys; Tulung, Golda J.; Lasut, Theresia M.C (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â Â ABSTRACTÂ Â Â This research is entitled â€œUniversity Studentsâ€™ Perception on the Influence of Instagram Use in Learning Englishâ€. The objectives of this research are to identify the ways in which university students use Instagram to learn English based on the theory of Freeman & Andersonâ€™s (2011) and to analyze the university studentsâ€™ perception about the influence of Instagram use in learning English based on the theory of Gibson et al (2009). A qualitative method with open-ended-interview is the method used to identify and analyze the university studentsâ€™ perception on the influence of Instagram use in learning English. The writer collected the data at Sam Ratulangi University, specifically at the English Department in Faculty of Humanities. The result showed that the university students use Instagram to learn English in many ways, since Instagram can be used both as providing teaching resources and enhanced learning experience. Moreover, most of the university students have positive perceptions on the influence of Instagram use in learning English based on the five factors of stereotype, selectivity, self-concept, needs and emotions.Keywords: University studentsâ€™ perception, Influence of Instagram use, Learning English